Dual near-infrared fluorescence-based lateral flow immunosensor for the detection of zearalenone and deoxynivalenol in maize. (30th January 2021) - Jin, Yongpeng; Chen, Qian; Luo, Sunlin; He, Lidong; Fan, Ruiqi; Zhang, Siwei; Yang, Chunjiang; Chen, Yiqiang
Highlights: A novel dual near-infrared fluorescence-based lateral flow immunosensor was developed. This immunosensor can simultaneously determine zearalenone and deoxynivalenol on a single test line. The limit of detection of this immunosensor is lower than most other documented bio-analytical method. The assay time of this immunosensor is less than 20 min. Abstract: A novel dual near-infrared fluorescence-based lateral flow immunosensor was developed to determine zearalenone and deoxynivalenol in maize. Two near-infrared dyes with distinct fluorescence characteristics were utilized to separately label the anti-zearalenone and anti-deoxynivalenol antibodies as detection reagents. The capture antigens zearalenone-BSA and deoxynivalenol-BSA were mixed and immobilized on the same test line of nitrocellulose membrane. This assay format facilitates simultaneous detection of the two mycotoxins on a single test line. After optimizing experimental parameters, the limits of detection for zearalenone and deoxynivalenol were as low as 0.55 μg/kg and 3.8 μg/kg in maize, respectively. The spiking experiment yielded recovery ratios ranging from 81.7% to 107.3% with coefficients of variation less than 14% demonstrating high assay accuracy and precision. Moreover, the actual sample analysis produced consistent results between this method and instrumental method. Therefore, the developed immunosensor can serve as an accurate and efficient approach for monitoring mycotoxins in agricultural products.